Pengaruh Brand Ambassador Dan Diskon Terhadap Perilaku Konsumen Dalam Berbelanja Di Tokopedia (Studi Kasus Pada Mahasiswa Unisma Malang) - Afriyanti, Fitri; Wahono, Budi; Novianto, Abdullah Syakur (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study aims to analyze the influence of brand ambassadors and discounts on consumer behavior in shopping through the e-commerce platform Tokopedia, particularly among students of the Islamic University of Malang (Unisma). The research is motivated by the rising trend of online shopping and increasingly diverse marketing strategies, including the use of brand ambassadors and discount offers. This study employs a quantitative descriptive method using a survey approach. Data were collected through questionnaires distributed to 100 active Tokopedia users. The results of multiple linear regression analysis indicate that brand ambassadors and discounts simultaneously have a significant effect on consumer behavior. Partially, both brand ambassadors and discounts also significantly influence consumer behavior, with significance values below 0.05. The study concludes that marketing strategies such as employing suitable public figures and offering attractive discounts can enhance consumer interest and purchasing decisions in online shopping. These findings are expected to serve as a reference for e-commerce companies in developing effective marketing strategies tailored to the characteristics of Generation Z. Keywords: Brand Ambassador, Discount, Consumer Behavior, Tokopedia, E-Commerce